The Effect of Mirror Therapy on Improving Limb Function in Post-Stroke Patients with Hemiparesis: a Narrative Review - Muhamad, Sahrul Nur; Widianti, Efri; Nursiswati, Nursiswati (Journal of Nursing Care, 2024)
Stroke is a global health problem and deaths. Stroke with hemiparesis can cause long-term disability if not treated properly. Intervention with the right therapy can prevent various obstacles, one of which is mirror therapy which is an intervention method that is cheap, easy, safe, and can be done independently. However, the review of comprehensive studies is limited. This study aimed to determine the benefits of mirror therapy on the extremity function of post-stroke patients who had hemiparesis. This study used a narrative review approach basaed on PRISMA 2020 guidelines. Searching article were conducted in four databases, namely PubMed, CINAHL, Sage Journal, and Google Scholar, with the keywords were mirror therapy, Stroke rehabilitation, post-stroke, hemiparesis, and stroke. Inclusion criteria in this study were stroke patients with hemiparesis, randomized controlled trial (RCT) research design, quasi-experimental and clinical trials, using English and Indonesian, full-text articles available in 2012-2022, with the outcome of the study were quality of life, increased extremity motor function, cognitive, emotional and reduce the patient's pain. Results: twelve articles show the effect of mirror therapy in post-stroke patients who experience hemiparesis and the review notes that mirror therapy has a positive effect on motor improvement which has an impact on increasing the ability to carry out daily activities, preventing depressive disorders, and improving the quality of life of patients. The combination of the application of conventional rehabilitation therapy, neuromuscular electrical stimulation, and the use of virtual reality-based mirror therapy can enhance the therapeutic effect. Conclusion: Mirror therapy can be used as a therapeutic recommendation that can improve limb function in post- stroke patients. More research is needed by meta-analysis to find more comprehensive evidence.Keywords: Hemiparesis, Mirror Therapy, Post Stroke